Construction of the hit-deficient mutant strain of Streptococcus mutans ATCC25175 - LAI Yangfan (Editorial Department of Journal of Prevention and Treatment for Stomatological Diseases, 2021)
Objective To construct a hit-deficient mutant strain of S. mutans ATCC25175 and verify its cell cycle regulatory function. Method Genomic DNA was extracted from S. mutans ATCC25175 strains, and then the upstream and downstream DNA fragments of the hit gene were cloned into the pFW5 vector (spectinomycin resistant) to construct recombinant plasmids using PCR amplification. Third, employed by natural genetic transformation in S. mutans ATCC25175 strains, the linearized recombinant plasmids were transformed into their genetic competence, induced by the synthesized competence-stimulating peptide (CSP), and then, homologous recombination was utilized to produce crossover and noncrossover products. Fourth, the hit-deficient mutant strains of S. mutans ATCC25175 were screened through the spectinomycin-resistance marker and identified by the electrophoresis of PCR products and PCR Sanger sequencing. Finally, its growth rate in vegetative BHI medium was also investigated. Results The upstream (856 bp) and downstream (519 bp) DNA fragments of the hit gene from the genomic DNA materials of S. mutans ATCC25175 were cloned into two multiple cloning sites (MCS-I and MCS-II) of the pFW5 vector, respectively, and the recombinant plasmid pFW5_hit_Up_Down was constructed and identified by double-emzyme digestion and PCR Sanger sequencing. The linearized recombinant plasmids were transformed into their genetic competence, induced by the synthetic CSP, and then, homologous recombination was utilized to produce various products. The hit-deficient mutant strains of S. mutans ATCC25175 were screened through the spectinomycin resistance marker and identified by the electrophoresis of PCR products and Sanger sequencing. The growth rate of the hit-deficient mutant strains versus their parental S. mutans ATCC25175 strains was increased greatly (P<0.001). Conclusion The hit-deficient mutant strains of S. mutans ATCC25175, having heritable traits, were successfully constructed, and the encoding Hit protein is growth-phase regulated in the cell cycle.